On the Backstepping Approach for VSC-HVDC and VSC-MTDC Transmission Systems. Issue 5 (16th March 2017) - Ayari, Mohamed; Belhaouane, Mohamed Moez; Jammazi, Chaker; Braiek, Naceur Benhadj; Guillaud, Xavier
Abstract: This article presents a backstepping control design strategy for the voltage source converter (VSC)-based high-voltage direct current (HVDC). First, a dynamic model is derived based on the state space description. Subject to the backstepping control design procedure strategy, a non-linear control scheme is developed in the sense of Lyapunov stability theory in order to satisfy various objectives of a stable HVDC system and guarantee a grid connection with a unity power factor. Then, the proposed control method is extended for multi-terminal (MT) HVDC transmission systems based on VSCs. In order to improve the dynamic behavior of the controlled DC bus voltage and the stability of MTDC systems, a backstepping control strategy accorded to each VSC is proposed and integrated into the voltage droop control strategy. The designed advanced controller allows to improve the overall DC grid stability and to reach the droop values, designed on static considerations, with satisfying dynamic behavior. Compared to the conventional control, the use of a backstepping control allows to exhibit excellent transient response over a wide range of operating conditions.